Insulin non-persistence among people with type 2 diabetes: how to get your patients to stay on insulin therapy. Issue 4 (19th May 2018) - Garnero, Theresa L.; Davis, Nichola J.; Perez-Nieves, Magaly; Hadjiyianni, Irene; Cao, Dachuang; Ivanova, Jasmina I.; Peyrot, Mark
ABSTRACT: Continuing use of medication is key to effective treatment and positive health outcomes, particularly in chronic conditions such as diabetes. However, in primary care, non-persistence (i.e. discontinuing or interrupting treatment) with insulin therapy is a common problem among patients with type 2 diabetes. To help primary care physicians manage patients who are non-persistent or likely not to be persistent, this review aimed to provide an overview of modifiable and non-modifiable factors associated with insulin non-persistence as well as practical strategies to address them. Data were extracted from published studies evaluating factors associated with non-persistence among patients with type 2 diabetes. A targeted literature review was performed using PubMed to identify recent studies (2000–2016) reporting measures of non-persistence with insulin therapy. Practical strategies to identify and prevent non-persistence were based on the authors' direct experience in primary care. Non-modifiable factors associated with non-persistence included gender, age, prior treatments, and cost of therapy. Before/at insulin initiation, modifiable factors included patients' perception of diabetes, preference for oral medication, and concerns/expectations about treatment complexity, inconvenience, or side effects. After initiation, modifiable factors included syringe use, difficulties during the first week of therapy, side effects, and insufficient glycemic control. Open-ended and patient-centered questions and a blame-free environment can help physicians identify, prevent, and reduce non-persistence behaviors. Possible questions to start a conversation with patients are provided. Effective physician-patient communication is essential to the management of diabetes. Primary care physicians should be familiar with the most common reasons for insulin non-persistence.